PENDAMPINGAN MANAGEMENT LEADERSHIP DI KELOMPOK BISNIS “BISNIS KITA” SAWOJAJAR, KOTA MALANG, JAWA TIMUR - Ririn Noviyanti (Bulletin of Community Service and Development, 2022)
Purpose of the study: the realization of strong online business and has high competitiveness and the realization of an online business that is able to survive in various seasons and at all times. Methodology: The method used is mentoring including field studies, observation and evaluation, coordination meetings, mentoring and socialization. Main Findings: During the service process, partners understand how important management leadership is that is indispensable and beneficial for every individual business person. Applications of this study: Partners had an increased sales turnover after mentoring activities that are useful for every individual business person. Novelty/Originality of this study: In this service, the discipline to dare to continuously care for the fostered team to achieve common goals and work as a team is an important factor for business continuity.